Dairy cow parity affects relationships among nutritional parameters in the blood of dams, umbilical cords, and calves and placental development at calving - Riku MASHIMO; Hanon OHBAN; Yuka KUMAZAKI; Sayaka ITO; Tomono KATAGIRI; Nobuyuki KUSABA; Chiho KAWASHIMA (The Society for Reproduction and Development, 2024)
Heifer growth and milk production in lactating cows may diminish the nutrient supply to the fetus. This study aimed to analyze the characteristics of the nutrient supply to the fetus in primiparous and multiparous cows. We investigated maternal, umbilical cord, and calf blood glucose and amino acid levels, as well as placental development in 28 primiparous (PP) and 30 multiparous (MP) Holstein cows. Although the total cotyledonary weight and surface area showed no significant differences, the MP group exhibited larger individual cotyledons (P < 0.01) and fewer medium-sized cotyledons (P < 0.05). Within the PP group, total cotyledonary weight and surface area positively correlated with blood glucose (r = 0.71-0.77; P < 0.01) and total essential amino acid (r = 0.55; P < 0.05) concentrations in the umbilical veins. However, no significant correlation was observed in the MP group. Blood glucose and amino acid concentrations in the umbilical vein, umbilical artery, and calf were significantly lower in the MP group (P < 0.05), although no difference was observed in the dams between the groups. In conclusion, the nutrient status of primiparous cows can alter fetal nutrient supply. Moreover, multiparous cows have larger individual cotyledons as an adaptive response to increased milk production during pregnancy. However, this adaptive response in multiparous cows did not completely restore nutrient supply to the fetus to the same extent as that in primiparous cows. Therefore, the nutritional management of multiparous cows during pregnancy must be reconsidered.